Respuesta :

We have the following general rule for the slope of the line given two points on it:

[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]

in this case, we have the following information:

[tex]\begin{gathered} m=\frac{1}{2} \\ (x_1,y_1)=(3,4) \\ (x_2,y_2)=(1,y) \end{gathered}[/tex]

if we use the formula, we get:

[tex]\begin{gathered} \frac{1}{2}=m=\frac{y-4}{1-3} \\ \Rightarrow\frac{y-4}{-2}=\frac{1}{2} \end{gathered}[/tex]

next, we have to solve for y:

[tex]\begin{gathered} \frac{y-4}{-2}=\frac{1}{2} \\ \Rightarrow y-4=-2\cdot\frac{1}{2}=-1 \\ \Rightarrow y=-1+4=3 \\ y=3 \end{gathered}[/tex]

therefore, y = 3

ACCESS MORE